2021
DOI: 10.3389/fcimb.2021.637836
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Phenotypic Characterization of Hsp90 Phosphorylation Sites That Modulate Virulence Traits in the Major Human Fungal Pathogen Candida albicans

Abstract: The highly conserved, ubiquitous molecular chaperone Hsp90 is a key regulator of cellular proteostasis and environmental stress responses. In human pathogenic fungi, which kill more than 1.6 million patients each year worldwide, Hsp90 governs cellular morphogenesis, drug resistance, and virulence. Yet, our understanding of the regulatory mechanisms governing fungal Hsp90 function remains sparse. Post-translational modifications are powerful components of nature’s toolbox to regulate protein abundance and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…However, for plant pathogens it is not established in detail, which otherwise might be critical for virulence. Four of these proteins have various role as: (i) stress-induced-phosphoprotein 1 {STIP1, also known as heat shock protein 70/90 (HSP70/90)} is known to regulate different cellular and physiological processes including cell morphology, drug resistance, and virulence in eukaryotes ( Singh et al, 2009 ; Alaalm et al, 2021 ). (ii) Acetyl-CoA acetyltransferase (encoded by Pt homologous CDS c55520_g1_i2), also denoted as ERG10 or Acetoacetyl-CoA thiolase or thiolases, contributes in biosynthesis of isopropanoid that expedites conversion of mevalonate to ergosterol through mevalonate pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, for plant pathogens it is not established in detail, which otherwise might be critical for virulence. Four of these proteins have various role as: (i) stress-induced-phosphoprotein 1 {STIP1, also known as heat shock protein 70/90 (HSP70/90)} is known to regulate different cellular and physiological processes including cell morphology, drug resistance, and virulence in eukaryotes ( Singh et al, 2009 ; Alaalm et al, 2021 ). (ii) Acetyl-CoA acetyltransferase (encoded by Pt homologous CDS c55520_g1_i2), also denoted as ERG10 or Acetoacetyl-CoA thiolase or thiolases, contributes in biosynthesis of isopropanoid that expedites conversion of mevalonate to ergosterol through mevalonate pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed that GAS had no significant effect on Hsp90 expression, which suggests that GAS inhibited Hsp90 ATPase activity and had no effect on protein expression. Several studies have reported that the activation of Hsp90 by phosphorylation is very important [35][36][37]. The phosphorylation of Hsp90 governs its interactions with co-chaperones and client proteins and could affect its stability.…”
Section: Discussionmentioning
confidence: 99%
“…The switch from the inactive to the active (and vice versa ) is driven by allostery. 59,87,88 Allostery can be triggered by noncovalent or covalent binding events, 88–112 leading to conformational and dynamic changes, 36,41,94,95,113–120 by inciting local energetic frustration, or conflicts. 25,121–123 Conformational changes relieving the frustration propagate in the structure, shifting the ensemble from the inactive toward the stable, minimally frustrated active state (Fig.…”
Section: Allostery Is a Hallmark Of Function If No Protein Conformati...mentioning
confidence: 99%